Психологічні чинники відчуження неповнолітніх правопорушників - Александров, Ю. В.; Aleksandrov, Y. V.; Шиліна, А. А.; Shylina, A. A.; Шиліна Алла Андріївна (Габітус. - 2021. - Вип. 30. - С. 217-221, 2021)
Проаналізовано поняття «відчуження», психологічні підходи до розуміння даного феномену, а також розкрито суть та зміст толерантності до невизначеності, її види та проблеми формування. Досліджено специфіку відчуження неповнолітніх правопорушників з різними формами відчуження, а також особливості толерантності до невизначеності. Виявлено, що досліджувані неповнолітні правопорушники з такими формами відчуження, як безсилля, нігілізм та авантюризм, мають специфічні особливості окремих проявів відчуження та толерантності до невизначеності.

The article considers the problem of alienation and certain psychological factors that may affect it, in particular, tolerance for uncertainty. The concept of deviant behavior in adolescents, in particular the psychological characteristics of juvenile offenders. The concept of alienation, psychological approaches to understanding this phenomenon are analyzed, as well as the essence and content of tolerance to uncertainty, its types and problems of formation are revealed. We believe that the position of the adolescent in relation to uncertainty when he either accepts uncertainty, or sees it as a source of threat to himself, is a regulator of his behavior in situations that cause alienation. To solve this question, such psychodiagnostic methods were used as the questionnaire of subjective alienation of V.M. Kosyrev’s educational work, and the method “New questionnaire of tolerance to uncertainty” by T.V. Kornilova. The experimental study involved juvenile offenders who were divided into three groups depending on the dominant form of alienation, namely powerlessness, nihilism and adventurism. The specifics of alienation of juvenile offenders with different forms of alienation, as well as the features of tolerance to uncertainty and the relationship between alienation of juvenile offenders and tolerance to uncertainty were studied. In particular, it was found that the studied juvenile offenders with forms of alienation of powerlessness, nihilism and adventurism have specific features of certain manifestations of alienation and tolerance for uncertainty. It was found that the more severe the form of alienation in the studied juvenile offenders, the more they show alienation in various spheres of life. The study of certain aspects of tolerance / intolerance to uncertainty showed that the more severe the form of alienation inherent in a group of juvenile offenders, the more they express intolerance to uncertainty, and, conversely, the easier form of alienation inherent in juvenile offenders intolerance to uncertainty.

Проанализированы понятия «отчуждение», психологические подходы к пониманию данного феномена, а также раскрыта сущность и содержание толерантности к неопределенности, ее виды и проблемы формирования. Исследована специфика отчуждения несовершеннолетних правонарушителей с различными формами отчуждения, а также особенности толерантности к неопределенности. Выявлено, что исследуемые несовершеннолетние правонарушители с такими формами отчуждения, как бессилие, нигилизм и авантюризм имеют специфические особенности отдельных проявлений отчуждения и толерантности к неопределенности.
Psychological factors of alienation of juvenile offenders
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Юридична психологія. Legal psychology. Юридическая психология; Україна. Ukraine. Украина; неповнолітні правопорушники; juvenile offenders; несовершеннолетние правонарушители; відчуження; alienation; отчуждение; інтолерантність; intolerance; интолерантность; толерантність до невизначеності; tolerance for uncertainty; толерантность к неопределенности; форми відчуження; forms of alienation; формы отчуждения; психологічні чинники; psychological factors; психологические факторы